2011
DOI: 10.2174/138161211797247541
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Gene Transfer to the Liver

Abstract: The liver acts as a host to many functions hence raising the possibility that any one may be compromised by a single gene defect. Inherited or de novo mutations in these genes may result in relatively mild diseases or be so devastating that death within the first weeks or months of life is inevitable. Some diseases can be managed using conventional medicines whereas others are, as yet, untreatable. In this review we consider the application of early intervention gene therapy in neonatal and fetal preclinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 164 publications
(194 reference statements)
1
10
0
Order By: Relevance
“…Gene therapy has achieved correction or amelioration of the clinical manifestations of many genetic diseases in animal models and in some human patients. Neonatal gene transfer has the advantages of achieving therapeutic effects before disease manifestation, a low vector requirement and high vector-to-cell ratio, and a relatively immature immune system (Waddington et al, 2004;Ponder, 2007;McKay et al, 2011). However, vigorous cell proliferation in the newborn stage is a significant challenge for nonintegrating vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy has achieved correction or amelioration of the clinical manifestations of many genetic diseases in animal models and in some human patients. Neonatal gene transfer has the advantages of achieving therapeutic effects before disease manifestation, a low vector requirement and high vector-to-cell ratio, and a relatively immature immune system (Waddington et al, 2004;Ponder, 2007;McKay et al, 2011). However, vigorous cell proliferation in the newborn stage is a significant challenge for nonintegrating vectors.…”
Section: Introductionmentioning
confidence: 99%
“…However, a limitation in the therapeutic use of rAAV is the loss of episomal vector genomes from actively dividing cells resulting in transient expression of therapeutic transgenes [46][47][48] . Hence, the combination of genome editing technology with rAAV-mediated delivery could lead to permanent genome modification and positive therapeutic outcome in young patients when tissues, such as the liver and retina, are still growing 19,49 .…”
Section: Potent In Vivo Genome Editing Using An All-in-one Raav Vectomentioning
confidence: 99%
“…In addition, multiple gene therapy studies have indicated that muscle tissue may be more prone to the development of humoral and/or cytotoxic immune response, ultimately resulting in elimination of the therapeutic protein (Warrington and Herzog, 2006 secrete a myriad of proteins. Treatment of neonatal animal models with liver-targeting vectors has been successful for several LSDs including mucopolysaccharidosis (MPS) I and MPS VII; however, treatment of more mature/adult animals has proven more challenging, primarily because of the more robust immune response in mature animals (Ponder and Haskins, 2007;McKay et al, 2011). For example, in the mouse model of Pompe disease, antibodies elicited in response to gene therapy completely abrogated cross-correction of other distal tissues (Cresawn et al, 2005;Warrington and Herzog, 2006;Koeberl et al, 2007).…”
Section: Cross-correctionmentioning
confidence: 99%
“…At these very young ages, the immune system is immature and introduction of foreign proteins at this time could allow for tolerization to the therapeutic product (Ponder, 2007;McKay et al, 2011). Furthermore, another advantage to initiating treatment at this age is that disease pathology is likely less severe.…”
Section: Complications Of Gene Therapy For Lsdsmentioning
confidence: 99%